Evaluate the Effect of Biosynthesized Silver Nanoparticles on Wound Healing in Experimental Mice - Neihaya H. Zaki (Journal of Global Pharma Technology, 2016)
Biosynthesized silver nanoparticles showed a change in solution color from light yellow to dark brown after 24hr incubation. Results of Ag-NPs characterized by Scanning electron microscopy showed oval, rectangle particles and the average size is 35.1 nm. X-ray diffraction shows one high peak at 2ø (32.5°) as standard XRD data of nano-silver crystals. Antibacterial activity of Ag-Nps against pathogenic isolates of E. coli, P. aeruginosa, Klebsiella pneumoniae and Staph. aureus was shown as inhibition zones (11, 12, 14 and 11) mm respectively. There are no toxicity of Ag-Nps in treated mice, and no significant changes nor clinically significant changes observed in the body. Ag-Nps (10mM) showed significant reduction in incision wound for 7 days. Actions of Ag-Nps on wound healing in mice provided a new therapeutic direction for wound treatment in clinical apply. Keywords: Biosynthesis of Ag-Nps, E.coli, Antibacterial activity, Wound Healing.